2022
DOI: 10.1039/d1tc05929g
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a luminescent square-like Cd6Eu2 nanocluster for the quantitative detection of 2,6-dipicolinic acid as an anthrax biomarker

Abstract: Two Cd-Ln (Ln = Ho(III) and Eu(III)) complexes 1 and 2 were synthesized using two organic ligands. The square-like Cd6Eu2 nanocluster 2 exhibits luminescence response to DPA through the enhancement...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Recently, we found that some Eu(III) complexes with Schiff base ligands could be used as fluorescent sensors to detect DPA. 23,24 A common method for the synthesis of metal clusters is the use of polydentate organic ligands bearing oxygen or hybrid oxygen−nitrogen donor atoms to bridge metal ions, for example, carboxylates, 25 alkoxides, 26 and phosphonates. 27 In our previous study, some 14-and 42metal nanoclusters containing pure 4f ions were constructed from polydentate vanillin-type ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we found that some Eu(III) complexes with Schiff base ligands could be used as fluorescent sensors to detect DPA. 23,24 A common method for the synthesis of metal clusters is the use of polydentate organic ligands bearing oxygen or hybrid oxygen−nitrogen donor atoms to bridge metal ions, for example, carboxylates, 25 alkoxides, 26 and phosphonates. 27 In our previous study, some 14-and 42metal nanoclusters containing pure 4f ions were constructed from polydentate vanillin-type ligands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The reasons can be explained as follows: (a) It is improved by the antenna effect of TEAH + . That is, there is an effective intramolecular energy transfer from TEAH + to the activated Mn 4+ ions [21,22] . (b) The size of organic cations will directly affect the Mn−Mn spacing in inorganic blocks, and the increase of Mn−Mn spacing inhibits the energy transfer of Mn−Mn, then leads to the gradual enhancement of QY i [42–44] …”
Section: Resultsmentioning
confidence: 99%
“…That is, there is an effective intramolecular energy transfer from TEAH + to the activated Mn 4 + ions. [21,22] (b) The size of organic cations will directly affect the MnÀ Mn spacing in inorganic blocks, and the increase of MnÀ Mn spacing inhibits the energy transfer of MnÀ Mn, then leads to the gradual enhancement of QY i . [42][43][44] Influence of Mn 4 + and TEAH + concentrations on emission intensity…”
Section: Photoluminescence Properties At Room Temperaturementioning
confidence: 99%
See 2 more Smart Citations